2017
DOI: 10.1038/s41598-017-14887-8
|View full text |Cite|
|
Sign up to set email alerts
|

Character-based DNA barcoding for authentication and conservation of IUCN Red listed threatened species of genus Decalepis (Apocynaceae)

Abstract: The steno-endemic species of genus Decalepis are highly threatened by destructive wild harvesting. The medicinally important fleshy tuberous roots of Decalepis hamiltonii are traded as substitute, to meet the international market demand of Hemidesmus indicus. In addition, the tuberous roots of all three species of Decalepis possess similar exudates and texture, which challenges the ability of conventional techniques alone to perform accurate species authentication. This study was undertaken to generate DNA bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 57 publications
(62 reference statements)
0
11
0
1
Order By: Relevance
“…Resulting amplicon is sequenced to identify genetic differences and species are identified. Mishra et al 8 examined the efficacy of recommended barcode markers rbcL, matK, trnH-psbA, ITS and ITS2 in differentiating three congeneric species of the genus Decalepis. They also examined the ability of these markers to separate Decalepis spp.…”
mentioning
confidence: 99%
“…Resulting amplicon is sequenced to identify genetic differences and species are identified. Mishra et al 8 examined the efficacy of recommended barcode markers rbcL, matK, trnH-psbA, ITS and ITS2 in differentiating three congeneric species of the genus Decalepis. They also examined the ability of these markers to separate Decalepis spp.…”
mentioning
confidence: 99%
“…By reviewing the main DNA barcoding studies performed in this family, we found contrasting opinions on which region is the most recommended, as the type of analysis (intragenus vs. intergenera) seems to greatly influence the suitability of the barcoding region. However, several works recognized a higher efficiency in the combined use of plastidial and nuclear markers ( Selvaraj et al, 2015 ; Mishra et al, 2017 ; Lv et al, 2020 ). For this reason, we chose both the plastidial rbc L region – one of the two core barcodes established by the Consortium for Barcode of Life, (CBOL; CBOL Plant Working Group, 2009 ) – and ITS1, a supplementary nuclear barcode candidate suggested again by the CBOL.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that reliable species differentiation would not be possible for24% of the species in the rbc L dataset and 32% in the trn L dataset. However, limitations have also been reported in other DNA-barcode studies such as [19, 48and 30]. Gill et al ., (2019) [19] reported a barcode gap for only 73% of the species investigated for the rbc L primer and 79% for the trn L-F primer in their barcode library for the semi-arid eastern South African Savanna plants.…”
Section: Discussionmentioning
confidence: 99%